Qumran archaeology: skeletons with multiple personality disorders and other grave errors - Zias, Joseph E. (Revue de Qumran, 2003)
Following the discovery of the Dead Sea Scrolls in 1947, and the excavations of R. De Vaux (1949-56) Qumran continues to attract wide public attention. As a result of the site's prominence, it has also fostered widespread scientific abuse, lawsuits and unverified claims by scholars and non-scholars alike since the 1960's. The recent excavations (2000-2002), which continue to make headlines with claims of discovering James the Brother of Jesus, John the Baptist, Teacher of Righteousness, The Overseer and a zinc coffin, are examples of the lack of scientific integrity which continues to plague the archaeology of Qumran.